Internet Utilization and Income of Entrepreneurs in the Informal Sector - Christiana Dyah Ratnasari (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2021)
The presence of the informal sector gives rise to more disadvantages in the economic development of a country, and individuals working in this sector are more vulnerable to poverty. However, technology plays an important role in decreasing the extent of informality and increasing work productivity. This study was conducted to examine the extent to which the use of the Internet in the job activity of entrepreneurs in the informal sector could increase their income. Using data from the Indonesian Labor Force Survey 2019–2020 and ordinary least square regression method, this study reveals that the use of the Internet significantly correlates with an increase in income by 11.8%. The effect was found to be 12% higher among entrepreneurs in the non-Java regions than in Java regions. Meanwhile, male entrepreneurs were noted enjoy a 14% greater benefit than female ones.